HUMAN RESOURCE DEVELOPMENT IN HEALTH CENTERS TO IMPROVE THE QUALITY OF PUBLIC HEALTH SERVICES - Muhammad Ary Aprian Noor; Meiske Claudia (CV. Adiba Aisha Amira, 2025)
The conjunction is that the implementation of health human resource management has not been optimal, especially human resource development in health centers. The literature article review of human resource development in health centers to improve the quality of public health services aims to find out how to implement human resource development in health centers to improve the quality of public health services. The method of writing this Literature Review article is by library research, which is sourced from online media such as Google Scholar and literature books. The result of this review literature article is that the implementation of human resource development in health centers is a strategic step to improve the quality of public health services by designing the right program, using effective learning methods, conducting periodic evaluations and utilizing digital application technology so as to contribute to providing the best health services to the community